Naturalizing Culture: An Analysis of Human and Nature Communication in Peatland Management in Pelalawan Regency - Novriyanto, Bambang; Naini, Albert Muhammad Isrun (UIR Press, 2026)
Peatlands are ecologically sensitive and highly flammable ecosystems. This study analyzes human-nature communication in forest and peatland management in Teluk Meranti District, Pelalawan Regency, Riau Province, Indonesia, within the framework of a sustainable economy. The region is characterized by extensive peatlands with significant potential for agriculture and plantation development. However, unsustainable land clearing practices, particularly burning, pose serious environmental risks. Using a qualitative approach and a case study method, this research investigates how local communities interpret natural signs and apply traditional ecological knowledge in managing forests and peatlands. The study is guided by Donal Carbaugh’s concept of Naturalizing Culture, which emphasizes the integration of cultural practices with environmental stewardship. Findings reveal that land burning remains a traditional method of land preparation, but it is governed by local norms such as staged burning, the construction of firebreaks, and crop diversification to preserve ecological balance. The use of intercrops such as pineapples, areca nuts, and vegetables emerges as a strategic approach to sustainable economic development. This study underscores the development of a human-nature communication model that harmonizes local wisdom with environmental stewardship, providing a strategic approach for sustainable peatland management